PERAN GURU DALAM MENGATASI PERILAKU TANTRUM PADA ANAK USIA DINI DI DAY CARE SEKOLAH DOLAN PERUMAHAN VILLA BUKIT TIDAR MALANG - Dwi Wasilah Wati; Khoirul Asfiyak; Mutiara Sari Dewi (Jurnal Dewantara, 2021)
This study aims to describe the conditions and factors of children with tantrums, analyze the strategies used by teachers in overcoming tantrums at Dolan School Day Care, analyze teacher barriers. The method used by researchers is to use qualitative research. The instrument used by the researcher is the presence of researchers, observation sheets, recording equipment, and research stationery. Location of Villa Bukit Tidar Housing Block A4 No.209. The conclusions in this case are (1) the conditions and factors of children behaving in tantrums at Dolan School Day Care, namely children easily cry, whine, get angry, roll on the floor and scream, this condition is called manipulative tantrums with the child's desire not being fulfilled, Children cannot express their desires in the form of language and the environment at school or at home. (2) the strategies applied by teachers and caregivers in dealing with children's tantrum behavior are to let the child but with supervision until his anger subsides, give him simple directions or advice, and ask parents about parenting at home. (3) the obstacles experienced by teachers at Dolan School Day Care in dealing with children who behave in tantrums are the home environment that always obeys all the wishes of the child, the playground environment, children who behave difficult to control, the teacher's lack of understanding about tantrum behavior, inadequate facilities and infrastructure. adequate, and the lack of teaching staff.